'Producing musicians like sausages': new perspectives on the history and historiography of Venezuela's El Sistema. (8th August 2018) - Baker, Geoffrey; Frega, Ana Lucía
ABSTRACT: A powerful and eulogistic narrative has evolved around the Venezuelan National System of Youth and Children's Orchestras, better known as El Sistema. Recently, however, critical perspectives have begun to emerge from the academic sphere. Nevertheless, researchers have faced an acute shortage of documentary resources relating to the programme's history. The reappearance of a collection of documents from 1996 to 97 thus represents an important development. The sources, which include four external evaluations, relate to El Sistema's efforts to secure funding from the Inter-American Development Bank. In this article, these documents are examined in chronological order and then analysed in comparative perspective. They shed light on both the history of El Sistema and polarised present-day debates about this famous organisation, corroborating recent academic studies and further questioning the dominant institutional and advocacy narrative about a socially transformative programme aimed primarily at the poor.